PELATIHAN OPERASI–PERAWATAN MESIN PENGADUK BUMBU HEXAGONAL UNTUK EFISIENSI PRODUKSI: EVALUASI PRA–PASCA PADA UMKM KERIPIK PRODUK KUMBOKARNO OLE-OLE DESA JAJAR - Wahyu Dwi Lestari; Hendra Maulana; Praja Firdaus Nuryananda; Mufida Diah Lestari; Isynariyah Zein; Rahmad Ady Febriansyah; Rafif Zaidan Althafiansyah; Dana Afif Azizullah; Kemas Achmad Fikri (Jurnal Abdi Insani, 2025)
MSMEs chips in Jajar Village still manually layer seasoning, resulting in long processing times, high operator workload, and inconsistent quality between batches. This community service program aims to shift the process to a hexagonal seasoning mixer while simultaneously instilling discipline in operation-maintenance (PM) SOPs to increase efficiency and quality consistency. The activity implementation method includes needs mapping, SOP-module preparation, training (theory, demonstration, practice), coaching on the production floor, and pre-post evaluation. Instruments include pre-post knowledge tests, operator skill checklists, and process indicator measurements (productivity, CV of seasoning homogeneity, seasoning defects, setup time, unplanned downtime, and SOP/K3 compliance). The results showed a relative increase in operator knowledge of 63.6% (55% → 90%) followed by simultaneous improvements in process indicators: productivity increased by 29.1% (28.5 → 36.8 kg/hour), coefficient of variation (CV) of homogeneity decreased by 35.6% (17.4% → 11.2%), seasoning defects decreased by 57.6% (8.5% → 3.6%), setup time decreased by 31.5% (16.5 → 11.3 minutes), unplanned downtime decreased by 38.7% (62 → 38 minutes/day), and SOP/K3 compliance increased by 32.4% (68 → 90). These results indicate that the combination of technology transfer, SOP standardization, preventive maintenance, and operational parameter assistance on the production floor is effective in increasing efficiency while maintaining quality consistency. This intervention is aligned with Asta Cita—specifically missions 3 (encouraging entrepreneurship and creative industries), 4 (developing human resources), 5 (downstream and industrialization), and 6 (building from villages), and supports the SDGs: SDG 8 (decent work & economic growth), SDG 9 (industry, innovation & infrastructure), SDG 12 (sustainable production & consumption), SDG 3 (health & well-being), and SDG 17 (partnerships).